Role of the railway-station zones in the spatio-functional development of Zagreb - Sić, Miroslav (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
This paper analyses the role of the railway-station zones in the spatio-functional development of Zagreb during two characteristic periods of its development: period of industrial urbanisation, and that of tertiary urbanisation. The zone of the main passenger railwaystation best shows the changes in the areasć purpose, as well as the trends of creating new functional structures of the central city.
Keywords: Zagreb; urbana geografija; mesta; urbanizacija; urbani razvoj; prostorski razvoj; železniški promet; postajališča